COMPARATIVE INVESTIGATION OF PHYSICAL ACTIVITY AND PHYSICAL FITNESS LEVELS OF STUDENTS ACCORDING TO HIGH SCHOOL TYPES - Uğurlu, Döndü; Çetin, Ebru (International Online Journal of Education and Teaching, 2023)
The present study aims to compare and examine the physical activity and physical fitness levels of students according to high school types. The sample consisted of 261 volunteer students with a mean age of (age=14.55±0.50year), including 129 female students (age=14.5±0.5year) and 132 male students (age=14.6±0.5year) from schools selected through convenience sampling according to high school types. Physical fitness measurements (cardiorespiratory endurance-1000 m, strength-right hand-left hand grip power, flexibility-sit and reach, body composition-age, height, weight, BMI, body fat percentage) and the International Physical Activity Questionnaire (IPOQ) were used for data collection. The evaluation of the study data was performed using the one-way ANOVA-Tukey test. In conclusion, according to the school types variable, it can be said that the physical fitness and anthropometric characteristics of sports high school students, who are thought to have more physical activity opportunities, are more developed. It was observed that physical activity was particularly effective in the development of cardiorespiratory endurance, one of the parameters of physical fitness.